Bike boys, drag queens, and superstars : avant-garde, mass culture, and gay identities in the 1960s underground cinema. - Suárez, Juan Antonio (Bloomington : Indiana Univesity Press, 1996)
Fonds Suzan Daniel (FSD)
Engels
Monografie